Stealth the ghost panther - Blade, Adam (Blade, Adam. Beast quest. Amulet of Avantia., 2012)
The evil Wizard Malvel's final Beast has reached the doors of King Hugo's palace! Stealth the Ghost Panther lassoes victims with his three tails, scratching the good citizens of Avantia and turning them into evildoers. To rescue his father, Tom must capture the final piece of Amulet from Stealth's collar--before all Avantia turns to evil!